The Momentum as a Systematic Risk Factor on the Bond Market: Evidence for the Croatian Government Bonds - Orlović, Zrinka; Dolinar, Denis; Zoričić, Davor (Ekonomický časopis/Journal of Economics, 2025)
This research objective is to examine momentum strategies in the less developed and less liquid Croatian bond market. Both “pure” kuna (domestic currency) and euro-denominated (currency clause embedded) government bond issues are considered for a period of more than 16 years. Starting with daily data on government bond prices and using monthly return observations, this research tries to identify the presence and strength of the momentum as the systematic risk factor on developing bond market. Sub-samples were also tested to examine how differ ent conditions, such as high and low interest rate levels, affect the performance of momentum strategies. The results support the possibility of creating profitable investment strategies based on the momentum for the sample of Croatian government bonds (assuming the possibility of short sale and ignoring transaction costs). Namely, statistically significant risk premiums are achieved for the most of analyzed holding periods.